2003
DOI: 10.1007/s11894-003-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing immunomodulator therapy for inflammatory bowel disease

Abstract: 6-Mercaptopurine (6-MP) and its prodrug azathioprine (AZA) remain the mainstay of immunomodulator therapy for the maintenance of steroid-free remission in patients with inflammatory bowel disease (IBD). Traditional dosing strategies for initiation of thiopurines are often based on weight or empirically chosen. Dosing based on an understanding of an inherited difference in drug disposition and metabolism may provide a safer alternative. The thiopurine methyltransferase (TPMT) enzyme plays a pivotal role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…Experience abroad has shown that AZA can be safely used for treatment of IBD [22][23][24] . Recently, TPMT and its genotype have been applied to predict the efficacy and toxicity of drugs, which can provide some guidance for clinicians and reduce the incidence of drug toxicity in Western countries [25][26][27][28][29] . Meanwhile, studies have shown that examining TPMT enzyme activity may decrease the overall medical cost in Europe and America [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Experience abroad has shown that AZA can be safely used for treatment of IBD [22][23][24] . Recently, TPMT and its genotype have been applied to predict the efficacy and toxicity of drugs, which can provide some guidance for clinicians and reduce the incidence of drug toxicity in Western countries [25][26][27][28][29] . Meanwhile, studies have shown that examining TPMT enzyme activity may decrease the overall medical cost in Europe and America [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The evidence supporting an upper limit of >450 pmol/8 Â 10 8 RBC is not so strong. The cutoff concentration above 450 pmol/8 Â 10 8 RBC is based on an increased risk of side effects (myelotoxicity 12 and nodular regenerative hyperplasia of the liver 15 ) without an increase in efficacy. Patients with erythrocyte 6-MMP concentrations above 5700 pmol/8 Â 10…”
mentioning
confidence: 99%
“…Patients with high TPMT activity may experience treatment failure (9,10 ) or hepatotoxicity (11 ), but the situation is much less clear than for the TPMT deficiencies (12)(13)(14). In addition, an estimated 10% to 30% of patients cannot tolerate AZA therapy because of nonmyelosuppression adverse reactions, such as influenzalike symptoms, nausea, vomiting, hepatotoxicity, pancreatitis, fever, or rash (1,12,15,16 ). Two recent studies with patients suffering from chronic inflammatory disease, a retrospective study by Marinaki et al (17 ) and a prospective one by von Ahsen et al (16 ), have provided evidence that deficiency in another polymorphic enzyme-inosine triphosphate (ITP) pyrophosphohydrolase (ITPA; EC 3.6.1.19)-could represent a further pathomechanism for thiopurine side effects in addition to TPMT.…”
mentioning
confidence: 99%